Livestock and Human Predation by Carnivores in Katerniaghat Wildlife Sanctuary, Uttar Pradesh, India - Sethy, Janmejay (International Journal of Bio-resource and Stress Management, 2023)
Based on information collected from the forest department and interviewing 153 households in five different villages with local people, a total of 21 human casualties and 288 livestock depredation were reported in different villages in Katerniaghat wildlife sanctuary during 2000-2007. During the study periods, out of 21 cases, 11 cases were killings and 10 cases were injured. Male casualties were more than the females. There was marked monthly and annually variation in the occurrence of human casualties. Among 21 cases, 11, 6, 3 and one casualties occurred in the age group of 21-30 years, 31-40, 41-50 and 11-20 years respectively. Highest number of 13 human casualties occurred between 1601-2000 hours. In the Katerniaghat wildlife sanctuary, Uttar Pradesh state, human population is constantly on the increase and as a result, there are increasing biotic pressure on protected areas and reserve forests. During the study periods, propose livestock growth programmes, including pasture improvement, and financial compensation as short-term measures to reduce conflict between people and predators. In the long-term, recommend that the feasibility of an insurance scheme should be tested, the possibility of relaxing the resource use restrictions in the Forest and Nature Conservation Act of 1995 be explored.